Analisis Kualitas Sumber Mata Air Desa Seraya Marannu Berdasarkan Parameter Fisika, Kimia, dan Biologi - Meiliza, Poppy Ratu; Ramdhoni, Kasyfi Amalul; Seno, Nathaniela Apdie; Gobel, Khaeriska Rahayu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The availability of clean water is a basic need that is very important for people's lives, especially in rural areas such as Seraya Marannu Village. This study aims to analyze water quality based on physical, chemical, and biological parameters in accordance with applicable standards. Physical parameters used the Gravimetric Method to determine total dissolved solids (TDS), while chemical parameters including pH, Total Hardness (CaCO3), COD, BOD, and Dissolved Oxygen (DO) used the Potentiometric Method (pH measurements were made using a pH meter), Titrimetric Method, Spectrophotometric Method, Dilution Method, and Direct Reading Method for each parameter. For biological parameters, Total Coliform analysis was conducted using the APHA 9221 B Method. The analysis results show that each parameter that has been analyzed produces parameter values that do not exceed the permissible quality standard limits, except for the pH parameter which is indeed when sampling, the sample is added with HNO3 until the pH of the solution is 2. This treatment aims to maintain the condition of the sample until the time of testing in the laboratory. For physical and chemical parameters, it is known that the Total Dissolved Solids value is 866 mg/L, pH 5, Total Hardness (CaCO3) 545.45 mg/L, COD 9.41 mg/L, BOD 2.7 mg/L, and Dissolved Oxygen (DO) 5.6 mg/L. It is also known that in the biological parameters the sample has a total coliform of 0 CFU/100ml so that the water sample is not suitable for consumption because it does not meet the quality standards based on Permenkes No.2 of 2023 concerning mandatory drinking water parameters. From the results of this study, it is hoped that the community can better understand the condition of the water sources they use and support better water management planning in the future.